Dynamic Fluid Responsiveness Assessment Using Pulse Pressure Variation in Intraoperative Spine Surgery Settings: A Case Report - Agus Aryanda Putra; Adinda Putra Pradhana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Vertebral metastases are a frequent complication in advanced malignancies, often presenting with severe pain and neurological impairment. This case report describes the perioperative anesthetic management of a 52yearold woman with breast cancer metastasis to the thoracic spine, scheduled for spinal decompression in the prone position. The patient presented with significant pleural effusion, thoracic vertebral compression, and decreased cardiorespiratory reserve. General anesthesia was induced and maintained using targetcontrolled infusions of propofol and remifentanil, with invasive monitoring through an arterial line and a central venous catheter. Intraoperative fluid responsiveness was evaluated using pulse pressure variation (PPV). Monitoring with PPV provides dynamic, realtime indicators that are highly reliable for predicting fluid responsiveness and help maintain hemodynamic stability without worsening pulmonary congestion or edema. PPV serves as a dynamic paramete influenced by the respiratory cycle and is particularly beneficial in mechanically ventilated patients. However, its accuracy may be affected by low tidalvolume ventilation, prone positioning, and pleural effusion. In this case, vigilant monitoring and prone positioning with a freehanging abdomen helped minimize confounding factors. The combination of PPV with clinical assessment and central venous pressure monitoring offered effective guidance for fluid therapy, enhancing intraoperative hemodynamic stability. Despite its limitations, PPV remains a valuable tool in perioperative fluid management, especially when integrated with other dynamic indices and a minifluid challenge. This case emphasizes the utility of PPV in complex oncologic spine surgery, where assessing fluid responsiveness is critical due to major bleeding, prone positioning, and mechanical ventilation.